The effects of transition and political instability on foreign direct investment inflows: Central Europe and the Balkans - Josef C. Brada; Ali M. Kutan; Taner M. Yigit (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper examines the effect of transition and of political instability on FDI flows to the transition economies of Central Europe, the Baltics and the Balkans. We find that FDI to transition economies unaffected by conflict and political instability exceed those that would be expected for comparable West European countries. Success with stabilization and reform tends to increase FDI inflows. In the case of Balkan countries, conflict and instability have reduced FDI inflows below what one would expect for comparable West European countries, and reform and stabilization failure have further reduced FDI to the region. Thus the economic costs of instability in the Balkans have been quite high.
Keywords: F21; F23; P52; 330; foreing direct investment; transition; political instability; political risk; Direktinvestition; Übergangswirtschaft; Länderrisiko; Schätzung; Osteuropa; Südosteuropa